Improving Economic Security through European Integration Reforms in Ukraine’s Social Sector - Tokarskyi, Т. (Економічний вісник Донбасу, 2020)
According to the Constitution of Ukraine (Article 1), Ukraine is a democratic, social and rule of law state. Developing a highly developed welfare state in Ukraine requires shaping its concept model and mechanisms of its functioning. Active and efficient social policy should become a solid foundation for comprehensive innovative, social development, integration into the European Union, the basis for developing a welfare state with a competitive socially oriented market economy capable of ensuring human development, decent standards and quality of life. This article substantiates the problem of ensuring the economic security of the state and suggests the ways to achieve European standards in the national social sphere. Ukraine has chosen the strategic course of the European integration as a priority of its domestic and foreign policy. This course provides for modernization of all spheres of life at the state and local levels in accordance with the broad context of the development strategy of the EU member states. Modern ideology, which is based on the principles of protection of citizens from major social risks (disability, impoverishment, etc.) and, partially, social paternalism, should be reconsidered in the context of principled of social inclusion. Improvement of existing approaches to social programming should start with a focus on the development and implementation of fundamental for social development state targeted programs on domestic and international social issues. Reorientation of domestic social policy requires correction of the forecast-monitoring system of implementation of multilevel social development programs, in particular state targeted programs in terms of revision of criteria for evaluating the effectiveness of social support programs.